1) 7^(x-2) > 49
7^(x-2) > 7^2
y = 7^x - возрастающая, т.к. а = 7, 7 > 1, тогда
х - 2 > 2
х > 2 + 2
х > 4
ответ: (4; + ∞ ).
2) 9^x - 3^x - 6 > 0
(3^x)² - 3^x - 6 > 0
Пусть 3^х = t (t > 0), тогда
t² - t - 6 > 0
D = 25
t1 = (1+5)/2 = 3;
t2 = (1-5)/2 = - 2
(t - 3)(t + 2) > 0
__+(-2)___-___(3)___+___x
t < - 2 - не удовлетворяет условию замены
или
t > 3
3^x > 3
y = 3^x - возрастающая, т.к. а = 3, 3 > 1, тогда
x > 1
ответ: (1; + ∞ ).
1) 7^(x-2) > 49
7^(x-2) > 7^2
y = 7^x - возрастающая, т.к. а = 7, 7 > 1, тогда
х - 2 > 2
х > 2 + 2
х > 4
ответ: (4; + ∞ ).
2) 9^x - 3^x - 6 > 0
(3^x)² - 3^x - 6 > 0
Пусть 3^х = t (t > 0), тогда
t² - t - 6 > 0
D = 25
t1 = (1+5)/2 = 3;
t2 = (1-5)/2 = - 2
(t - 3)(t + 2) > 0
__+(-2)___-___(3)___+___x
t < - 2 - не удовлетворяет условию замены
или
t > 3
3^x > 3
y = 3^x - возрастающая, т.к. а = 3, 3 > 1, тогда
x > 1
ответ: (1; + ∞ ).